0253 Sleep Patterns As A function of Breastfeeding: From Infancy to Childhood. (27th April 2018) - Pennestri, M; Laganiere, C; Pokhvisneva, I; Bouvette-Turcot, A; Steiner, M; Meaney, M; Gaudreau, H
Abstract: Introduction: Many studies have documented that breastfeeding has numerous benefits, both in children and in mothers, and the World Health Organization recommends exclusive breastfeeding for the first 6 months. During the same developmental period, parents are encouraged to teach their infant sleeping through the night: behavioral sleep interventions are proposed at an increasingly younger age. However, among the factors associated with sleep fragmentation, breastfeeding is often invoked. Whether sleep-wake patterns associated with feeding method in early infancy persist from infancy to childhood remains to clarify. This longitudinal study aims to assess sleep patterns from 6 to 24 months, as a function of feeding method at six months. Methods: Data were drawn from the Maternal Adversity, Vulnerability, and Neurodevelopment study (n=388). At 6 months, infants were divided into 2 groups, as a function of breastfeeding status (presence-absence). The longest consecutive sleep period and the total nocturnal sleep duration were assessed at 6, 12, 24, and 36 months with maternal reports. Sleep variables were compared with two-way ANOVAs with one independent factor (breastfeeding or not at 6 months) and one repeated measure (age). Results: At 6 months old, most infants were still breastfed (63%). There was a significant interaction between breastfeeding status at 6 months and age, on the longest consecutive sleep period (p<0.001). At 6 and 12 months, breastfed infants had a shorter longest consecutive sleep period than non-breastfed infants, (6:15 ± 2:49 vs 7:56 ± 2:49, p <0.001; 7:26 ± 3:16 vs 8:51 ± 2:52, p <0.001), with no difference at 24 and 36 months (p>0.05). There was no interaction between breastfeeding and age on total nocturnal sleep duration (p>0.05). While an age effect was present (p <0.001), no group effect was observed (p>0.05). Conclusion: Although breastfeeding at 6 months was associated with shorter consecutive sleep duration at 6 and 12 months, total nocturnal sleep duration was similar among the 2 groups at every timepoint. Parents should be informed that the transient sleep fragmentation associated with breastfeeding in infancy do not seem to impact total nocturnal sleep duration, nor long-term sleep-wake patterns. Support (If Any): McGill University